Case 2870: Xerophila geyeri Soos, 1926 (currently Trochoidea geyeri; Mollusca, Gastropoda): proposed conservation of the specific name - Gittenberger, Edmund (Bulletin of Zoological Nomenclature)
Acknowledgment of receipt published in BZN 50 (1): 2. Case published in BZN 51 (2): 105. Comments published in BZN 51(4): 336; 338, 52 (2): 176, 52 (3): 259, 52 (4): 331, 53 (1): 43; 43. Case closure notice published in BZN 77: 156